Inflammation in glomerular diseases - Xiong, Yongqing; Li, Wei; Jin, Songzhi; Wan, Shujing; Wu, Suzhen (Frontiers in Immunology, 2025)
The structural and functional integrity of glomerular cells is critical for maintaining normal kidney function. Glomerular diseases, which involve chronic histological damage to the kidney, are related to injury to glomerular cells such as endothelial cells, mesangial cells (MCs), and podocytes. When faced with pathogenic conditions, these cells release pro-inflammatory cytokines such as chemokines, inflammatory factors, and adhesion factors. These substances interact with glomerular cells through specific inflammatory pathways, resulting in damage to the structure and function of the glomeruli, ultimately causing glomerular disease. Although the role of inflammation in chronic kidney diseases is well known, the specific molecular pathways that result in glomerular diseases remain largely unclear. For a long time, it has been believed that only immune cells can secrete inflammatory factors. Therefore, targeted therapies against immune cells were considered the first choice for treating inflammation in glomerular disease. However, emerging research indicates that non-immune cells such as glomerular endothelial cells, MCs, and podocytes can also play a role in renal inflammation by releasing inflammatory factors. Similarly, targeted therapies against glomerular cells should be considered. This review aims to uncover glomerular diseases related to inflammation and pathways in glomerular inflammation, and for the first time summarized that non-immune cells in the glomerulus can participate in glomerular inflammatory damage by secreting inflammatory factors, providing valuable references for future strategies to prevent and treat glomerular diseases. More importantly, we emphasized targeted glomerular cell therapy, which may be a key direction for the future treatment of glomerular diseases.